Structural Equation Modeling of the Relationship between Media Literacy and Emotional Intelligence with Health Literacy (Case Study: Students of Azarbaijan Shahid Madani University) - Negin Saldar; Rahim Shahbazi (Tehran University of Medical Sciences, 2023)
Background and Aim: Health literacy plays a role in "reducing human casualties and financial costs" in a society. Emotional intelligence and media literacy also contribute to people's success in life. Therefore, the aim of this study was to investigate the mediating role of media literacy in the relationship between emotional intelligence and health literacy among graduate students of Azarbaijan Shahid Madani University.  Materials and Methods: This research is based on the nature and general characteristics, quantitative; Based on the purpose, it is applied and based on the research method and data collection method, is a descriptive correlation based on structural equation model. The statistical population was graduate students of Azarbaijan Shahid Madani University in 2020 (2218 students). The statistical sample of the research is 327 people who were selected by stratified random sampling method. To collect data, Emotional Intelligence Questionnaire (1998), Montazeri et al. Health Literacy Questionnaire (2014) and media literacy questionnaire were used. The reliability of the questionnaires was obtained using Cronbach's alpha coefficient of 0.91, 0.84 and 0.79, respectively. The collected data were analyzed using descriptive statistics and inferential statistics (structural equation model) using SPSS and LISREL software.  Results: The findings showed the mean of emotional intelligence, health literacy and media literacy of graduate students of Azarbaijan Shahid Madani University is 3.10, 3.47 and 3.58, respectively. Also, the results showed a significant relationship between emotional intelligence and students' health literacy. According to the findings, there is a significant relationship between emotional intelligence with media literacy, and media literacy with health literacy. Also, the media literacy variable plays a mediating role in the relationship between emotional intelligence and health literacy (coefficient) of 0.58 units. The results of the structural equation model test also showed that the proposed conceptual model fits the relationship between emotional intelligence, health literacy and students' media literacy.  Conclusion: Media literacy can not only directly affect students' health literacy, but also has a mediating role between emotional intelligence and health literacy. Due to the effect of emotional intelligence on students' health and media literacy, it is recommended that the necessary planning to be done in graduate education and to strengthen emotional intelligence.